Test diagnostique à l’entrée de l’enseignement supérieur : validation et usages - Marie-Claude Hublet; Sabine Lontie; Mohammed Arras; Sophie Remacle; Sylviane Bachy (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In the context of free access to higher education in Belgium and faced with a high failure rate, the Student Support Service of the Haute Ecole Vinci-Site Parnasse-ISEI has set up numerous measures to help success and guidance. Back-to-school diagnostic tests adapted to the diverse audiences of its paramedical, educational and social sections have been developed. They were validated by statistical analysis and on this basis, several uses of support of students and teachers are proposed.